2017
DOI: 10.1021/acs.jpcc.7b00533
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Activity of Nanoneedle Structured WO3 Photoanodes for Solar Water Splitting: Direct Synthesis via Chemical Vapor Deposition

Abstract: Solar water splitting is a promising solution for the renewable production of hydrogen as an energy vector. To date, complex or patterned photoelectrodes have shown the highest water splitting efficiencies, but lack scalable routes for commercial scale-up. In this article, we report a direct and scalable chemical vapor deposition (CVD) route at atmospheric pressure, for a single step fabrication of complex nanoneedle structured WO3 photoanodes. Using a systematic approach, the nanostructure was engineered to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 53 publications
5
67
0
Order By: Relevance
“…Therefore, to improvet he outdoor efficacy and indoor use of photocatalysts, researchers have attempted to develop materials with bandgape nergies that fall in the visible. [3] Various strategies have been applied in the development of visible-light active photocatalysts, including impurityd oping (e.g.,N:TiO 2 ), [4] surfacem odification (e.g.,p hosphates), [5] nanostructuring (e.g.,n anoneedles) [6] and the use of co-catalysts (e.g.,P t). [7] However,r ecent studies have shown that one of the most promising strategiesf or improving photocatalytic activity is to form ah eterojunction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to improvet he outdoor efficacy and indoor use of photocatalysts, researchers have attempted to develop materials with bandgape nergies that fall in the visible. [3] Various strategies have been applied in the development of visible-light active photocatalysts, including impurityd oping (e.g.,N:TiO 2 ), [4] surfacem odification (e.g.,p hosphates), [5] nanostructuring (e.g.,n anoneedles) [6] and the use of co-catalysts (e.g.,P t). [7] However,r ecent studies have shown that one of the most promising strategiesf or improving photocatalytic activity is to form ah eterojunction.…”
Section: Introductionmentioning
confidence: 99%
“…Photoelectrochemical (PEC) water splitting is one of the most promising approaches to store clean and abundant solar energy in form of hydrogen. This technology utilizes semiconducting materials such as BiVO 4 , Fe 2 O 3 , and WO 3 as photoanode to initiate the PEC process. The performance of semiconductor in this system depends strongly on the intrinsic properties of photoanode material as well as morphological properties of the thin film including surface roughness, structure (nanoparticles, nanorods, nanosheets, and so on), and film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that the longitudinal direction of 1D crystalline nanostructures can serve as a preferential pathway for electron migration . Nanotubes, nanorods, nanowires, nanofibers, and nanoneedles are among the typical 1D nanostructured photoactive semiconductors that have been grown on substrates for photoelectrochemical applications . Grimes and co‐workers demonstrated the presence of less‐localized charge carriers in a 1D nanostructure when compared to the same material in a 0D form which favored solar energy conversion applications .…”
Section: Similarities and Differencesmentioning
confidence: 99%